Развитие навыков критического мышления на уроках истории - Бондаренко, В.В. (My University, 2016)
"Critical thinking is a leading modern educational concept, relevant for the development of teaching and learning in Kazakhstan". Students need to teach children to think, not just to think but to think critically, as this kind of thinking can sensibly be judged on their actions and the actions of other people, to talk objectively, logically and consistently do, to take the point of view of other people, to admit their mistakes. The article provides examples of the use of techniques of critical thinking "Basket ideas", "Cluster", "keywords", "Mosaic", "6 hats" at different stages of a history lesson. These techniques are relevant to the realization of educational objectives in the contemporary context.
Keywords: critical thinking; techniques; information; comprehension; application; analysis; synthesis